Effect of Current Ratio, Inventory Turn Over and Time Interest Earned on Stock Prices in Cigarettes Sub-Sector Companies Listed on the Stock Exchange For the 2015-2019 Period - Elvina Elvina; Edi Gunawan; Holfian Daulat Tambun Saribu (Institute of Computer Science (IOCS), 2021)
This study aims to find out how the influence of Current Ratio, Inventory Turn Over and Time Interest Earned on Stock Prices in cigarette sub-sector companies included in the IDX list during 2015-2019. This research uses quantitative research methods, with data collection techniques using documentation studies. The data analysis model used is multiple linear regression analysis using the SPSS (Statistical Product And Service Solution) application version 23.0. there are a number of 4 companies that meet the criteria for a period of 5 years with the results of 20 research samples. The results of the analysis of research data reveal: partially: (1) Current Ratio has no influence on stock prices with a significance value of 0.117> 0.05. (2) Inventory Turn Over has no effect on the price as indicated by a significance number of 0.71>0.05. (3) Time Interest Earned has an influence on the Stock Price, which is indicated by a significance number of 0.010 <0.05. And simultaneously Current Ratio, Inventory Turn Over, Time Interest Earned affect stock prices with a significance number of 0.016 <0.05